European territorial development and the place based approach: the budgetary dimension of Portugal 2020 - Ferreira, Filipe Eduardo Miranda; Catarino, João Ricardo (Iberoamerican Journal of Development Studies, 2018)
Territory has been taken as one of the main dimensions of the process of formulation and implementation of public policies. This article is based on the concept of public policy territorialisation as stated by the IFDR (2010) when referring to the place based approach as the new international paradigm of regional policies. This study aims to describe the possible benefits of these policies in the face of previous regional development European policies (OECD, 2009: 50) and assess, based on the Portuguese case, if there is an effective correspondence between the theoretical framework of place based policies, as they are formulated (Barca, 2009), and the actual implementation of territorial instruments, in the case of Portugal 2020, by mobilizing the budgetary dimension.This study is relevant because the place based policies are changing the formulation mode of territorial development policies in many countries and regions, so it is important to understand associated benefits and risks. In this study, we describe these advantages and elaborate an analysis of the effective correspondence between the formulation and its practical implementation in the European Union, by analysing the Portuguese case (Portugal 2020), from the viewpoint of resources allocated. Naturally, at the heart of European concerns, is the fight against regional imbalances without losing sight of the difficult task of maintaining the financial sustainability of the European budget and achieve fiscal consolidation, particularly in a context of global crisis (Catarino & Alcario, 2016 Catarino, 2015 and Catarino & Fonseca, 2013)It was found that the place based instruments identified in the Portugal 2020 represent 11% (EUR 2 billion to EUR 18 billion) of regionalized funds and 7.6% (EUR 2 billion to EUR 26 billion) of the total received by Portugal. It is concluded that there is no correspondence between the place based formulation of the current territorial development policies cycle of the European Union for the period 2014-2020 and its effective implementation of Portugal 2020. This confirms the hypothesis that there is a dysfunction between theory and practice, not validating the advantages referenced in the scientific literature about the place based policies.
Keywords: European Regional Policy; Cohesion Policy; Place based policy; Portugal 2020